Bioactivity of the extract from an endophytic fungi nigrospora Oryzaisolated from pterolobium Hexapetalum-(roth.) - S. ASHWINI; KALYANARAMAN RAJAGOPAL (International Journal of Pharma and Bio Sciences, 2016)
Nigrospora oryzae an endophytic fungus isolated from the leaf of a climber Pterolobium hexapetalum (Roth.) Sant and Wagh. produced bioactive compound which are active against human pathogens. The organic extract (ethanol) of the endophyte Nigrospora oryzae was separated using HPLC and tested for biological activities. The ethanol extract was tested for antibacterial and anti fungal activity using agar well diffusion method. The extract of Nigrospora oryzae was active against Streptococcus pneumoniae, Salmonella typhi and Candida albicans. The extract showed maximum zone of inhibition against Salmonella typhi (19.2±0.2 mm) and C. albicans (15.6± 0.41mm) at the volume 100µg /ml.